Speech Production in EFL Classrooms: A Psycholinguistic Study of Planning and Fluency - Muhammad Faisal Hajmi; Natasya Miranda Gihar; Laila Anum; Yani Lubis (Asosiasi Dosen Muda Indonesia, 2026)
This study investigates speech production in EFL classrooms from a psycholinguistic perspective, with a focus on planning and fluency. Many EFL learners experience difficulty speaking fluently even when they possess adequate grammatical and lexical knowledge. This study aims to explain these difficulties by examining the cognitive processes involved in real-time speech production. A qualitative research design was employed involving undergraduate EFL students. Data were collected through classroom speaking tasks, audio recordings, semi-structured interviews, stimulated recall sessions, and field notes. The analysis focused on patterns of speech planning, lexical retrieval, monitoring behavior, and fluency disruption. The findings reveal that excessive planning, slow lexical access, strong focus on form, and low automaticity significantly reduce fluency. Learners often plan and monitor their speech simultaneously, which increases cognitive load and leads to frequent pauses, hesitation, and self-repair. The results indicate that fluency problems stem primarily from processing constraints rather than lack of language knowledge. This study highlights the importance of incorporating psycholinguistic principles into EFL speaking instruction. Teaching practices should address planning load, reduce over-monitoring, and support the development of automaticity to improve spoken fluency.